2023
DOI: 10.1007/s41024-023-00301-6
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive reuse of vernacular built heritage: learnings from Alcino Cardoso House (1971–1991) by Álvaro Siza

Abstract: The Alcino Cardoso House (first phase: 1971–1973; second phase: 1988–1991), located in northern Portugal, was one of the first interventions in pre-existing buildings undertaken by the Pritzker Prize-winner architect Álvaro Siza (1933) to receive national and international acclaim. The design consisted of the conservation of vernacular farm buildings and their transformation into a holiday home and tourist accommodation. This intervention echoes the concerns of the critical revision of modern architecture in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The authors acknowledge the support and collaboration of the following individuals and institutions: Eleonora Fantini, Miguel Frias Coutinho, and Tiago Trindade Cruz, who participated in the research for the case study of Alcino Cardoso House [95][96][97]; Beatriz Filipe, Eleonora Fantini, Hugo Mendonça, and Daniel Duarte Pereira, for the production and artwork of the analytical drawings; the Atelier of Eduardo Souto de Moura and Luís Ferreira Alves, for providing drawings and photographs; the Marques da Silva Foundation, Casa da Arquitectura, the Serralves Foundation, and the Canadian Center for Architecture, for providing access to their archives and graphic materials; to the owners of the buildings (especially Clemente Menéres Semide, Sofia Thenaisie, and Zilda Cardoso) for allowing us access and providing us with valuable information.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…The authors acknowledge the support and collaboration of the following individuals and institutions: Eleonora Fantini, Miguel Frias Coutinho, and Tiago Trindade Cruz, who participated in the research for the case study of Alcino Cardoso House [95][96][97]; Beatriz Filipe, Eleonora Fantini, Hugo Mendonça, and Daniel Duarte Pereira, for the production and artwork of the analytical drawings; the Atelier of Eduardo Souto de Moura and Luís Ferreira Alves, for providing drawings and photographs; the Marques da Silva Foundation, Casa da Arquitectura, the Serralves Foundation, and the Canadian Center for Architecture, for providing access to their archives and graphic materials; to the owners of the buildings (especially Clemente Menéres Semide, Sofia Thenaisie, and Zilda Cardoso) for allowing us access and providing us with valuable information.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…All these constitute tangible and intangible cultural traditions which reflect in the built heritage of countries. Ferreira1 et al have observed that traditional built heritage forms a paradigm of sustainability as they combine the preservation of cultural values and collective identities together with landscape integration (Ferreira, 2023). Ardhyanto, et al have concluded that vernacular architecture serves as a historical testament, encapsulating the values of a community and reflecting their evolution and agreements over time .…”
Section: Review Of Literaturementioning
confidence: 99%